The Influence of Visual Art in Irwan Jamal’s Theatre Artistic Vision - Oktavianti, Yeni Sari; ., Jaeni; Saleh, Sukmawati (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
Irwan Jamal, the founder of the Pictorial Theatre and the Casanova Theatre, is an artist who has studied several art disciplines at once, including theatre, visual arts, literature, and music. Genetic influences from his father’s family, who are skilled in drawing, as well as his education and experience in theatre, have resulted in a form of theatre that is rich in visual expression. This is based on Sigmund Freud’s theory of primary creativity which grows and becomes the foundation of one’s creativity. This article will also discuss and analysed the influence of the visual arts on Irwan Jamal’s vision of theatrical creations in terms of the several works he has directed, both theatrical productions as well as films and music videos. Irwan Jamal’s artistic vision and expression, which was later categorized as a form of “expressionist theatre” was very strongly influenced by the fine arts that Irwan Jamal also studied. The method used to analyse Irwan Jamal’s works (theatre and music videos) will also use the formal structure criticism method, which is usually used for the analysis of a painting. The presentation of critical works uses the method introduced by Edward S Feldman.